Effects of spermidine polyamine on metabolism and longevity (Research, Society and Development, 2022)
The polyamine spermidine is found in all eukaryotic beings and in most prokaryotes. According to their polycationic nature, polyamines can easily join negatively charged biomolecules, especially DNA, RNA, proteins and phospholipids, modifying in many occasions the function of these macromolecules. Given their ability to bind to other molecules, they are associated in several functions, mainly linked to growth, autophagy, survival and cell proliferation. The aim of this study was to identify the effects of spermidine polyamine on metabolism and longevity.  This is an integrative literature review study, using the following databases SciELO, PUBMED, LILACS and journals of the Coordination for the Improvement of Higher Education Personnel (Capes). In addition to the induction of autophagy, the actions of spermidine have been related to the modulation of reactive oxygen species, DNA replication, transcription and translation, anti-inflammatory properties, modified mitochondrial activity, enhanced proteostasis, and hypusination growth. Polyamines have a complex and diffuse relationship to disease. They can be harmful, neutral or beneficial, varying according to the polyamine and the specific disease. However, it appears that spermidine expressed more positive effects, being in agreement with its expressed beneficial effects on lifespan and stress.